MON-169 Diagnostic Utility of Free Cortisol in Dexamethasone Suppression Test. A Prospective Study in Healthy Subjects - Athimulam, Shobana (J Endocr Soc, 2020)
OBJECTIVE: Low dose dexamethasone suppression testing (DST) is standard of care in patients with adrenal incidentalomas or suspected endogenous hypercortisolism. False positive total serum cortisol (TC) results occur due to poor absorption, rapid metabolism or estrogen use. Free serum cortisol (FC) measurement is an alternative, but optimal cut-offs are unknown. We aimed to establish the optimal serum dexamethasone concentrations (DEXA) to interpret TC and FC results and identify reasons for discrepancies between TC and FC values in healthy male and female (with and without oral contraceptive therapy, OCT) subjects. METHODS: Single center prospective study of healthy subjects >17 years old undergoing assessment with DST between 2016 and 2019. Measurement of FC and DEXA was performed by tandem mass spectrometry and TC by immune-enzymatic assay at 8 AM following overnight administration of 1 mg dexamethasone at 11pm. Subjects were excluded if they had a known adrenal adenoma, any form of endogenous cortisol excess, or exogenous steroid use. RESULTS: DST was performed in 165 healthy volunteers, median age of 29.5 (18-74) years; 53 men (32%) and 112 (67%) women, median BMI 25 (18-42) kg/m(2), 47 (42%) of which were taking OCT (median daily ethinyl-estradiol dose of 30 (20-35) mcg). The median DEXA was 0.34 (0.09-1.12) mcg/dl, median TC was 0.8 (0.25-15.7) mcg/dl and median FC was 24 (4-714) ng/ml. TC and FC measurements were highly correlated (r(2)=0.89, p<0.0001). The median FC/TC was 3% (0.3-6.7), lowest in women on OCT (median 2.5% vs 3.3% in women not on OCT and men, p<0.0001). TC>1.8 mcg/dl was demonstrated in 18 (11%) healthy subjects (men: 3/53, 5.7% vs women not on OCT: 3/65, 4.6% and women on OCT: 12/47, 25.5%, p=0.0007). Excluding women on OCT, the proportion of subjects with TC>1.8 was higher when DEXA was <0.2mcg/dl (4/15, 27%) vs when DEXA was >0.2mcg/dl (2/101, 2%),(p<0.0001). After excluding 24 (14%) healthy subjects with DEXA <0.2 mcg/dl, in the remaining 142 subjects (51 (35%) men, 54 (38%) women not on OCT and 39 (27%) women on OCT), median TC was 0.75 (0.25-4.6) mcg/dl and median FC was 23 (4-103) ng/ml). Significant differences were noted in both TC and FC following DST within subgroups: men vs women not on OCT vs women on OCT, TC: 0.6 vs 0.7 vs 1.3 mcg/dl, (p<0.0001) and FC: median 20 vs 22 vs 31 ng/ml, (p<0.0001). All men and all women not on OCT demonstrated post-DST FC <50 ng/ml (97.5% cutoff of 47 and 37), while women on OCT demonstrated post-DST FC <50 in 80% and FC<75 in 95%. CONCLUSION: Post-DST TC>1.8 mcg/dl was demonstrated in 11% of all healthy subjects, of which 1 in 4 were women on OCT and 1 in 4 had DEXA<0.2 mcg/dl. Simultaneous measurement of serum DEXA during DST may be valuable when false positive results are suspected. Despite a lower FC/TC ratio in women on OCT, post-DST FC cutoffs were higher in women on OCT. Measurement of FC after DST may be helpful in some but not all women on OCT.